How to Make Fast Arranging Article Draft into Journal Template Using Microsoft Word - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2024)
In scientific writing in the form of articles, the term template is often used. every author who would publish an article in a journal must change the draft format according to the journal template. Therefore, this research was conducted to discuss ways to do templates quickly using Microsoft Word. Some tools and materials must be prepared in doing the template, namely Microsoft Word, article draft, and journal templates. Based on the results and discussion it was found that in the template process, four steps must be carried out, namely blocking, copying, pasting, and checking. This research is expected to help authors who would adjust the format and move the article draft they make into the journal template.